REQUIREMENTS FOR A SOFTWARE MODEL THAT DEVELOPS STUDENTS’ INDEPENDENT LEARNING COMPETENCE (American Journal of Pedagogical and Educational Research, 2026)
This article provides a scientific and theoretical analysis of the requirements for a software model aimed at developing students’ independent learning competence. The increasing importance of independent learning in the modern education system is substantiated, and issues related to the effective organization of students’ activities through a digital learning environment are discussed. The article identifies constructivism, the competency-based approach, and adaptive learning principles as the pedagogical foundations of the improved software model. In addition, the functional capabilities of the model are clarified, including personalization, self-monitoring, prompt feedback, and requirements for an Uzbek-language interface. From a technical perspective, important aspects such as web architecture, mobile adaptability, database systems, and information security are examined. As a result, an integrated software environment model is proposed that supports the stages of independent learning, including motivation, planning, implementation, assessment, and reflection.